A step towards putting the students back into the academic language support model - Lim, Nena; Symons, Christine Elizabeth (Journal of Academic Language and Learning, 2018)
A decrease in the level of communication skills of university graduates has been a rising concern of educators worldwide. Responses to these concerns have produced literature that focuses on the kinds of academic language support educators can provide while the role of students has been downplayed. Attempting to fill this gap, this paper describes a model that emphasises the active role of students in the academic language learning process. This paper describes how a discipline academic and a language expert designed an accounting information systems course with the aim of integrating academic language skills into the course to improve the academic literacy skills of students. Apart from describing the details of the integrated academic support, the paper provides useful suggestions to educators on how to provide similar types of support to their students effectively.